Pricing to market of German exporters: evidence from panel data - Rahel Falk; Martin Falk (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1998)
This paper investigates price discrimination of German exporters across different foreign markets. We examine the degree of pass-through of exchange rate fluctuations in the pricing of 70 export items. The model is estimated using panel data on export unit values. Parameter estimation relies on GMM first difference, fixed effects, LAD, OLS first difference, and the random coefficients model. The main results for 70 manufactured goods and 15 destination countries between 1990-1994 are : The degree of pricing to market differs among destinations and products. Highest pricing to market is observed for U.S., Japan, Italy and Spain. Pricing to market is more prevalent in exports of chemicals and fertilisers than in machinery products.
Keywords: F12; L60; L13; F14; 330; Pricing to market; law of one price; panel data; Außenhandelspreis; Betriebliche Preispolitik; Exchange Rate Pass-Through; Internationaler Preiszusammenhang; Deutschland